Prognostic significance of body mass index and other tumor and patient characteristics in non-metastatic renal cell carcinoma - Ahmedov, Vusal; K?z?lay, Fuat; Cüreklibat?r, ?brahim (Urology Journal, 2018)
Purpose: In this retrospective study, we aimed to investigate the prognostic effect of body mass index (BMI) in localized renal cell carcinoma (RCC) cases who underwent surgical treatment. Furthermore, the assessment of various patient and tumor characteristics and surgical methods on survival has been identified as additional targets. Materials and Methods: Three hundred and eighty patients with localised, non-metastatic, unilateral RCC who underwent radical or partial nephrectomy in our clinic between January 2007 and December 2016 were enrolled in this study. Age, gender, height, weight, BMI, operation type and method, pathology results and tumor stage of the patients were recorded. Patients were divided into 3 groups according to body mass index (BMI): Normal weight (< 25 kg/m2), overweight (25-30 kg/m2) and obese (>30 kg/m2) as groups 1, 2 and 3, respectively. We analyzed the relation between the BMI, gender, smoking, hypertension, type and method of surgical treatment, histologic subtype, tumor stage, estimated glomerular filtration rate (eGFR) and cancer-specific (CSS) and recurrence free survival (RFS). All data analysis was performed using SPSS® Statistical Software for Windows (Version 13.0) and a P value less than 0.05 was considered to be significant. Results: The effect of BMI on both CSS and RFS was statistically significant (P < .001). There was also a significant relation between smoking, operation type (partial/radical), eGFR and tumor stage and CSS and RFS. Conclusion: Our findings show that overweight and obese RCC patients according to the BMI have a more favorable prognosis. Multicenter, prospective studies with more cases and longer oncological follow-up period are needed to support these findings.